Particle trapping and hopping in an optofluidic fishnet - Shi, Yuzhi (2019)
Particle jumping between optical potentials has attracted much attention owing to its extensive involvement in many physical and biological experiments. In some circumstances, particle jumping indicates escaping from the optical trap, which is an issue people are trying to avoid. Nevertheless, particle jumping can facilitate the individual trap in each laser spot in the optical lattice and enable sorting and delivery of nanoparticles. Particle hopping has not been seen in fluid because Fluidic drag force dramatically reduce the dwell time of particle or break the potential well. Here, we observe particle hopping in the microchannel by three reasons, e.g., particle collision or aggregation, light disturbing by pretrapped particle and fake trapping position. We show that commonly ignored particle influence to the light could create a new isolated trapping position, where particle hops to the adjacent potential well. The hopping happens in an optofluidic fishnet which is comprised of discrete hotspots enabling 2D patterning of particles in the flow stream for the first time. We also achieve a 2D patterning of cryptosporidium in the microchannel. Our observed particle hopping in the flow stream completes the family of particle kinetics in potential wells and inspires new interests in the particle disturbed optical trapping. The 2D patterning of particles benefits the parallel study of biological samples in the flow stream and have potential on cell sorting and drug delivery.